Effects of Ankaferd Blood Stopper and Celox on the Tissue Factor Activities of Warfarin-Treated Rats - YARAT, AYŞEN; GARİP, HASAN; GÖNÜL, ONUR (SAGE PUBLICATIONS INC, 2014)
The aim of this study is to evaluate the effect of these new generation hemostatic agents on early-stage soft tissue healing of warfarin-treated rats by measuring the tissue factor (TF) activities. Rats in the warfarin group were treated intraperitonally with 0.1 mg/kg warfarin, and rats in the control group were treated with 1 mL/kg saline. All rats had 3 incisions on dorsal dermal tissue applied Celox, Ankaferd Blood Stopper (ABS), or no hemostatic agent. Six rats from each group were killed on day 4, and the other 6 were killed on day 8. Prothrombin time (PT) and TF activities were evaluated, respectively. Both the hemostatic agents positively affected the hemostasis. Warfarin treatment increased the PT levels as expected. Celox-treated dermal tissues had higher TF activity when compared to ABS-treated ones. The ABS affected the early-stage healing positively in clinical aspect, whereas Celox was more effective on hemostasis by means of increasing TF activities.
Keywords: anticoagulants; chitosan; tissue factor; hemostasis; Ankaferd Blood Stopper; Celox; DENTAL EXTRACTIONS; THROMBIN; HEMOSTASIS; EFFICACY; CHITOSAN; TRIAL; TIME